Co-occurrence of online and offline bullying and sexual harassment among youth in Sweden: Implications for studies on victimization and health a short communication - Heléne Dahlqvist; Åsa Svensson; Katja Gillander Gådin (International Journal of Circumpolar Health, 2022)
Studies of co-occurrence of online and offline victimisation of bullying and sexual harassment and its associations to mental health outcomes among youth are scarce. To inform future study designs, the aim of this brief communication was to map co-occurrence of online and offline bullying and sexual harassment victimisation among adolescents. Data were collected in 2011 in nine schools in Northern Sweden, n = 1193 (boys = 566; girls = 627). Absolute and relative frequencies were calculated to find combinations of victimisation: one, two, three, or four forms. Reflecting a picture of the early days of online victimisation, in total fifty seven percent (57%) of adolescents were victimised. Single occurrence victimisation was 21.2% (offline sexual harassment was most common irrespective of gender), showing that most youths were victimised in a co-occurrence of two or more forms. Seven percent (7%) were victimised by all four forms of victimisation. Offline sexual harassment victimisation was present in the most common co-occurrences. Directions for future studies of victimisation and its associations to mental health outcomes are discussed.